Perceptions and Readiness of Elementary Teachers in Integrating Artificial Intelligence into Learning: Evidence from South Cikarang Indonesia - Hafifah, Dea Nur (International Journal of Education and Learning Studies, 2025)
This study investigates elementary teachers’ perceptions and readiness to integrate artificial intelligence (AI) into classroom practices in South Cikarang, Indonesia. Using a descriptive quantitative design, data were collected from 20 teachers across six schools through a validated questionnaire. Findings reveal generally positive perceptions, with high agreement on AI’s potential to enhance efficiency, creativity, and assessment support, alongside strong demand for training. Teachers emphasized AI as a supportive tool rather than a replacement, reflecting pragmatic optimism and relatively low concern about job displacement. However, institutional readiness remains uneven, with significant differences between public and private schools and across school contexts. The results highlight the need for targeted professional development, robust infrastructure, and clear governance frameworks to ensure AI adoption protects teacher agency while improving educational quality. The study also extends the Technology Acceptance Model by emphasizing institutional support as a key moderating factor.